STATIC WIND LOAD EVALUATIONS AND SAFETY ASSESSMENT OF ROOFING SHEET SYSTEMS IN MALAYSIA - KANG , SEAVHAI (2014)
Roofs of low rise buildings have been observed to fail in high wind events due to the comparatively less engineering input into their design. The damages will lessen if structural weaknesses on which the wind forces act can be eliminated. Damage to roofing has decreased significantly in Australia mainly due to the research and development work in Australia after cyclone Tracy. The steel roofing sheet systems have performed well under normal conditions of load where dead load and live load are the deciding factors. However, their performance under cyclonic wind loads has been disastrous. The predominant failure mode under such conditions is uplift. It is necessary to have guidelines on the suitability of a particular roofing sheet system for a particular wind zone. Though Malaysia doesn't have cyclones, it does have strong wind events which produce uplift failures in roofing sheet.